Historic changes of ecologically relevant hydrologic indices of unregulated Kansas streams - Aguilar, Jonathan P. (Kansas State University, 2009)
Over the past decades, it has been observed that the streamflow characteristics in the Great Plains rivers have substantially changed. These changes have affected and will continue to affect the management decisions within the watershed. This study was undertaken to document the changes for some unregulated streams in Kansas, characterize the streams in terms of some hydrologic indices, and identify the probable factors influencing the changes. Fourteen unregulated streams with 60 or more years of daily discharge data geographically distributed across the state were used. The analysis focused on hydrologic indices judged to be relevant to the lotic ecosystem. The state was divided into four regions, representing roughly the northwest, southwest, northeast and southeast sections of the state. Log Pearson III method was used for computing flow probabilities, Mann-Kendall test in conjunction with Sen’s slope estimator was used for trend analysis, whereas the indicators of hydrologic alterations software was used to generate most hydrologic indices. Several factors believed to affect the streamflow were identified, and their influence was modeled over time. A multi-variate statistical model was run. Results show that there is substantial difference in the streamflow characteristics between the western and eastern regions. Many streamflow aspects have changed over time, and a number of them show significant and important change. Most streams in western Kansas have longer and more frequent dry periods. Potential recharge rate, land use, water use, soil and water conservation practices, and soil type were significant factors influencing the median to very low flow, but the effect varied among the regions. Results of this study could be useful to decision makers, water users, watershed stakeholders, and environmental conservation advocates in addressing problems and concerns related to stream and river management.
Keywords: Historic change; Hydrologic index; Kansas streams; Streamflow; Hydrology; Unregulated stream; Engineering, Agricultural (0539)